Analisis Kebutuhan Pengembangan Buku Ajar Mata Kuliah Kearifan Lokal Pandhalungan - Afrizal, Mohamad; Citraningrum, Dina Merdeka (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2024)
Pandhalungan Local Wisdom is one of the courses offered by Muhammadiyah Jember University's Indonesian Language and Literature Education Study Program. Learning in this course has various challenges due to its newness, one of which is the lack of textbooks. This study aims to conduct a needs assessment of the textbooks for the course. The goals are to describe the competency criteria, student characteristics, student evaluation against the course, and subject matter suggestions for the course textbook. The results show that the characteristics of students are: 1) the average age of 20–21 years, which is classified as young adults; 2) knowledge of Pandhalungan: high category 50.11%, medium 32.33%, and low 17.56%; 3) perception of the benefits of course learning: very important 32.44%, quite important 52.22%, less important 15.34%; and 4) learning motivation: high 69.13%, medium 21.85%, low 9.02%. It is also concluded that the recommended subject matter for this textbook is eight topics: 1). Pandhalungan Culture and Identity; 2). Pandhalungan Cultural History.) Pandhalungan Art and Cultural Expression; 4) Pandhalungan Traditions and Rituals 5) Pandhalungan Cultural Diversity 6) Changes and Dynamics of Pandhalungan Culture 7) Preservation of Pandhalungan Culture; and 8) Culture and Communication of Pandhalungan Society